Contrastive and translational issues in rendering the English progressive form into Spanish and Catalan: an informant-based study - Espunya, Anna (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2001)
AbstractThis is a study on the formal correspondences for the English progressive in translations from English to Spanish and Catalan, with a special focus on the choice between simple and progressive forms. Its methodological approach includes the participation of informants both as translators and as evaluators of published translations. The paper discusses both the language-internal and task-related factors that play a role in the choice of verb forms.